Isolation, Definition and Chemical Control some of the Bacteria that Cause Contamination of Wall Paintings in Caves - El-Gorj, Fatma. M. A; Aisha, M. A.; Maznah, W.O. (Asian Journal of Pharmaceutical Research and Development, 2019)
Background: Caves are unique natural features and habitats where specialized organisms grow. One of the world’s main concerns is that of the conservation and preservation of our cultural heritage, including rock art and wall paintings within caves. Methods: This study was conducted by collecting the samples scraped from wall surfaces at 19 different location in painted caves of Niah cave, Sarawak, and Tempurung cave, Perak. Morphospecies identification and genomic DNA polymorphisms were used to identify the two strains of bacteria. The growth was controlled chemical method using sodium hypochlorite (NaOCl), Calcium hypochlorite Ca(OCl)2 and hydrogen peroxide (H₂O₂). Results: Morphospecies identification was carried out using a light microscopy and scanning electron microscopy (SEM), both the bacteria, bacteria I and bacteria II were isolated from the soil samples and were Gram-negative bacteria. Based on BLAST search, bacteria I showed 100% with Stenotrophomonas sp (NR 024708.1), and bacteria II showed 100% with Cryptococcus liquefaciens (NR 043289. 1). The growth was controlled chemical method using sodium hypochlorite (NaOCl), Calcium hypochlorite Ca(OCl)2 and hydrogen peroxide (H₂O₂). The laboratory studies showed that three chemical were effectively eliminated colonies/cells of the both bacteria compared to the colonies found on the control pate this study.